FTIR-Fingerprinting Spectra Combined with Chemometrics Analysis for Distinguishing Strobilanthes phyllostachya Leaves Extracts and Correlation with Their Antioxidant Activity - Rafi, Mohamad; Tohib, Devanka Aulia; Saputra, Agus; Aziz, Zuhelmi; Karomah, Alfi Hudatul (HAYATI Journal of Biosciences, 2025)
The leaves of Strobilanthes phyllostachya have a long history of use as a herbal medicine, and research has demonstrated that they contain a range of metabolites with antioxidant activity. This study will employ a chemometric approach to analyze the correlation between functional groups from Fourier Transform Infrared Spectroscopy (FTIR) spectra and antioxidant activity. The leaf samples will be extracted with water and ethanol at 30%, 50%, 70%, and ethanol p.a. Moreover, the extracts will be evaluated for their antioxidant activity and analyzed using FTIR spectroscopy. The antioxidant activity measurement results indicate that the 70% ethanol extract of S. phyllostachya exhibits the highest antioxidant activity. The IR spectra of the water and ethanol extracts exhibited slight differences in their patterns. While the spectra of the various ethanol extracts exhibited similarities, their absorption values differed. A principal component analysis with absorbance from the FTIR spectra at wavenumber 3400-2800 and 1800-1000 cm-1 gave a good cluster of different solvent extractions used in this study. The total variation of principal component-1 (PC-1) and PC-2 is 90%. The partial least square regression (PLSR) analysis results were used to correlate the absorbance value of FTIR spectra of S. phyllostachya extract with antioxidant activity. From the PLS-R analysis, we identified a functional group, i.e. carbonyl and hydroxyl, which significantly contributed to the antioxidant activity of the S. phyllostachya extract. The value of the R2 parameter, which assesses the goodness of fit, was found to be 0.9630, indicating that the PLSR model is good.